PITA RAJA (PENGETAHUAN DAN PELATIHAN BANTUAN HIDUP DASAR REMAJA AWAM TERAMPIL) MELALUI VIDEO DI DESA BINOH KEC. BURNEH - Januarti, Luluk Fauziyah; Yulianto, Sofi; Yulianto, Rahmad Wahyudi (STIKES NGUDIA HUSADA MADURA, 2025)
The right first aid in treating victims of cardiac arrest and respiratory arrest is by performing basic life support (BHD). Basic life support is the initial handling of victims of cardiac arrest and respiratory arrest. BHD knowledge and skills are important because they teach basic techniques for rescuing victims of various accidents or everyday calamities that are commonly encountered (Fajarwaty 2012). The purpose of this activity is provide knowledge to youth cadres in binoh village, burneh district about helping victims of cardiac arrest through basic life support (BHD). The method used in this activity was used lecture, demonstration, and simulation methods. This activity was carried out in Binoh village, Burneh sub-district in April 2025. The target of the activity is the youth cadre of Binoh village with a total of 42 people. The results obtained by the level of knowledge of cadres in the lecture and simulation education group before being given lay basic life support (BHD) education, namely obtained data on the level of knowledge of adolescents increased almost entirely in the good category 38 respondents (91.7%). The small portion was in the poor category as many as 4 respondents (8%). The next suggestion is that in order for this activity to continue, it is necessary to strengthen the youth cadres to continue to provide assistance and basic life support to residents who need help.